Gender differences in predictors of health status in patients with COPD - Tanni, Suzana Erico [UNESP]; Lucheta, Paulo Adolfo; Godoy, Irma [UNESP]; Faganello, Márcia Maria; Ferrari, Renata [UNESP]; Amaral, Renata Antonialli Ferreira do [UNESP] (Soc Brasileira Pneumologia Tisiologia, 2010)
Objective: To evaluate the health status (HS) of COPD patients and to identify the main predictors of HS in these patients according to gender. Methods: The study included 90 COPD patients (60 males and 30 females; mean age = 64 ± 9 years) with a wide range of airway obstruction disorders (mean FEV1 = 56 ± 19% of predicted). The men were individually matched to the women by % of predicted FEV1 (ratio: 2:1). The patients were assessed regarding body composition; six-minute walk distance; perception of dyspnea using the Modified Medical Research Council Dyspnea Scale; Saint George's Respiratory Questionnaire (SGRQ); Charlson comorbidity index; and the multidimensional Body mass index, airway Obstruction, Dyspnea, and Exercise capacity (BODE) index. Multiple linear regression analysis was performed to identify the predictors of HS by gender. Results: Impairment of HS was greater among the women than among the men for SGRQ total score and for all SGRQ domains (total: 51 ± 18% vs. 38 ± 19%; p = 0.002; symptoms: 61 ± 22% vs. 42 ± 21%; p < 0.001; activity: 62 ± 18% vs. 49 ± 21%; p = 0.004; and impact: 41 ± 19% vs. 27 ± 18%; p = 0.001). The multiple linear regression showed that age and perception of dyspnea correlated with SGRQ total score for both genders (males, r2 = 0.42; females, r2 = 0.70; p < 0.05). Conclusions: Our results showed an association between gender and HS in COPD patients. Age and dyspnea are determinants of HS in both genders.
Preditores do estado de saúde em pacientes com DPOC de acordo com o gênero
Keywords: Chronic obstructive; Dyspnea; Health status; Pulmonary disease